1911
DOI: 10.5962/bhl.title.30855
|View full text |Cite
|
Sign up to set email alerts
|

A first study of inheritance in epilepsy, by C.B. Davenport and David F. Weeks.

Abstract: The Frequency of the Different Classes of Mental Condition in the Children of two Mentally Defective Parents; together with the Mental Condition of the Grandparents, the Parents' Sibs (Brothers and Sisters) and Other Blood Relatives about Whom Something is Known.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1948
1948
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The role of knowledge leadership is to market a positive cultural orientation toward knowledge addition and knowledge sharing (Lee et al , 2014; Davenport et al , 1998; Davenport and Prusak, 1998; Davenport, 1997). Path goal theory of leadership has been developed to explain how behavior of a leader affects the subordinate in generating performance of the employees.…”
Section: Research Prototypementioning
confidence: 99%
“…The role of knowledge leadership is to market a positive cultural orientation toward knowledge addition and knowledge sharing (Lee et al , 2014; Davenport et al , 1998; Davenport and Prusak, 1998; Davenport, 1997). Path goal theory of leadership has been developed to explain how behavior of a leader affects the subordinate in generating performance of the employees.…”
Section: Research Prototypementioning
confidence: 99%
“…Davenport (13) recently found that a decrease of electrolyte concentration in RBC-influenza virus systems leads to a reduction in the elution rate of the virus. In the present study, when the NaC1 concentration of mixtures was reduced in experiments in which the stepwise elutlon technique was employed, a decrease in elution rate also was noted.…”
Section: Effect Of Increased Nacl Concentration Upon Elution Rate--imentioning
confidence: 99%
“…The 1-W-oleate-Freund (1) found that "mannide monooleate"' was an effective agent in combining antigens and mineral oils in the form of a water and oil emulsion. However, subsequent use has indicated an infrequent occurrence of cysts following injection of vaccines and allergens (2) made with certain lots of this surfactant. Berlin (3) performed studies which showed that the toxic reactions of a mineral oil-"mannide monooleate" emulsion may * Arlacel A, Atlas Chemical Industries, Inc., .…”
mentioning
confidence: 99%